Crystal structure of ethyl 1′, 5-dimethyl-2′′, 3-dioxo-3H-dispiro[benzo[b]thiophene-2, 3′-pyrrolidine-2′, 3′′-indoline]-4′-carboxylate. (2015) - Raja, R.; Govindaraj, J.; Suresh, M.; Raghunathan, R.; SubbiahPandi, A.
No abstract available